Draft Five Year Plan 1978-83 State Employment Programme Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
The programme has gained momentum during the period 1975-76-77-78, During this period 745 Educated unemployed have been established in Self Employment under this programme through the agency of Collectors. Apart from this seem 500 educated unemployed were earlier established through the agency of Madhya Pradesh Krishi- Udhyog Vikas Nigam. The total number of employment so far provided through state and Central programmes since the beginning of these schemes are 39687 out of which 30118 persons were Educated Unemployed.
Government of Madhya Pradesh, Planning, Economics and Statistics Department